ASSESSMENT OF THE IMPACT OF ECOLOGICAL FACTORS ON THE POPULATION OF SMALL MAMMALS OF THE LOWER AMU DARYA REGION (World Bulletin of Education and Learning, 2025)
In the article, the influence of environmental factors on the population of small mammals (Microtus Ilaeus) in the lower reaches of the Amu Darya River was determined. According to the obtained results, the quantitative dynamics of the Microtus Ilaeus population is controlled by the following parameters: the structure and size of the previous population, b) the current state of the population, weather conditions, food availability, humidity of the territory, and the hydrological regime of the Amu Darya River. It has been proven that the effectiveness of the influence of weather and density factors on population dynamics has seasonal characteristics.
Keywords: Environment, ecological factors, dynamics, population, hydrological regime, temperature